Criminalidade juvenil: significados e sentidos para “reincidentes” em Medidas Socioeducativas de Internação no Estado do Paraná - Souza, Luciano Aparecido de (2016)
This research aims to analyze the meaning and the sense that "recidivists" in Measure Socioeducative of deprivation of liberty paranaenses give to the recidivism and the manner in which they relapsed. This is a qualitative and quantitative, exploratory and descriptive approach, operationalized through the bibliographical and documentary research and through the semi-structured interview. The theoretical and methodological, empirical and documentary guidance that illuminates the logical procedures followed is the hermeneutics-dialectics. The research describes and contextualizes the main legal-normative and theoretical-practical instruments that currently regulates and inform, in the State of Paraná, the type of state intervention consubstantiated in institutions, policies, professional practices and specialized agents that comprise the Socioeducative System of the State of Paraná, pointing out conservation of a institutional and material structure of the penal modernity, hidden from the perspective of a "universal childhood" and operated by an alleged "politicalinstitutional reorganization" which extended the use of imprisonment as an a institutional response to the juvenile violence and crime, starting, first, of the idea of "resocialization" and, then of the ideas of "prevention" and management of "risk factors". The results indicate a criminal selectivity focused on race distinction and on class distinction, where the "recidivists" on Measure Socioeducative of deprivation of liberty represent 17.5% of adolescents in "fulfillment" of that same Measure Socioeducative. It is young (92.7% between 16 and 18 years) non-whites (61.8%), male (98.2%), with low education (74.5% in Phase II of the Elementary School ), excluded from the labor market (81%), from dispossessed families (49% receive between 1 and 2 minimum wages) and of precarious areas of large urban centers (80%). The "nature" of the infractions attributed to the "recidivists" confirms the predominance of a "street criminality" (76.3%) highlighting the illegal acts typified as crimes against property (robbery: 41.2%) and against public safety (drug trafficking: 21.4%). The so-called "violent crimes" (crimes against persons) equals to 13.4% of all infractions attributed to the "recidivists". The research shows that deprivation of freedom prevents access of individuals to the socialization processes, belonging, recognition and otherness necessary for their emancipation. Privileging the interview with "key informants" and the constitution of their trajectories and life experiences (both in relation to the institutions and social organizations and with the institutions of deprivation of liberty), the research confirms that the deprivation of liberty, besides withdraw the subject of the your circles of relationships and of the your symbolic exchanges systems, preventing their full development, reproduces social injustices and stigmatization, causing suffering unnecessary, alienation, control, segregation and neutralization.